KNOWLEDGE WORKERS’ MANAGEMENT - Ramona TODERICIU; Alexandra STANIT; Anca SERBAN (Risk in Contemporary Economy, 2014)
The empirical research of this paper deals with knowledge workers in Romanian organizations from different fields of activity, with the purpose of distinguishing them from other types of employees and clarifying their profile and individual characteristics. Also, the paper presents the most important challenges concerning the knowledge workers’ management: identifying, developing and evaluating knowledge workers, motivating and rewarding them, as well as describing specific structure of the organizations that rely mostly on knowledgeable workforce. The findings of the research represent an important factor in developing future efficient human resources strategies and practices regarding workers that fuel the knowledge economy.